The effect of foreign direct investment on financial development : empirical evidence from Bahrain - Abdalmajeed Alsmadi, Ayman (Array, 2019)
The aim of this paper is to analyze the relationship between foreign direct investments and financial development in Bahrain. The estimation financial development effects was performed for the period 1978 to 2015, which covers the political conflicts that recently happened in Middle East area (Arab Spring). On the other hand, the paper sought to examine the causality relationship between foreign direct investments and financial development. The study empirically investigates the short and long run equilibrium relationship between the variables by applied co-integration and Autoregressive Distributed Lags Approach (ARDL). The Granger causality test was employed to capture causality relationship. The obtained results show that there is a significant positive relationship between FDI and financial development in short and long run, while, a significant negative relationship between Arab Spring and financial development. However, the results also revealed bidirectional causality relationship between FDI and financial development.